2005
DOI: 10.1164/rccm.200409-1243oc
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Primary Graft Dysfunction on Survival after Lung Transplantation

Abstract: Rationale: Primary graft dysfunction is a severe acute lung injury syndrome after lung transplantation. Long-term outcomes of subjects with primary graft dysfunction have not been studied. Objectives: We sought to test the relationship of primary graft dysfunction with both short-and long-term mortality using a large registry. Methods: We used data collected on 5,262 patients in the United Network for Organ Sharing/International Society of Heart and Lung Transplantation registry between 1994 and 2000. We asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
214
0
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 308 publications
(225 citation statements)
references
References 23 publications
3
214
0
8
Order By: Relevance
“…Twenty-eight patients were excluded because of missing mPAP is primary graft dysfunction (PGD), a severe, acute lung injury occurring early after lung transplantation that is responsible for significant morbidity and mortality. [11][12][13][14][15][16][17][18][19][20] While previous studies have demonstrated that primary PAH is known to be a risk factor for PGD, [14][15][16]21 the role of secondary PAH in PGD risk is incompletely understood. The purpose of this study was to evaluate the association between mPAP and the development of severe PGD in patients with IPF who underwent lung transplantation.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-eight patients were excluded because of missing mPAP is primary graft dysfunction (PGD), a severe, acute lung injury occurring early after lung transplantation that is responsible for significant morbidity and mortality. [11][12][13][14][15][16][17][18][19][20] While previous studies have demonstrated that primary PAH is known to be a risk factor for PGD, [14][15][16]21 the role of secondary PAH in PGD risk is incompletely understood. The purpose of this study was to evaluate the association between mPAP and the development of severe PGD in patients with IPF who underwent lung transplantation.…”
Section: Resultsmentioning
confidence: 99%
“…The main reason for PGD is ischaemia/reperfusion (I/R) injury, clinically manifesting within a spectrum from mild acute lung injury (ALI) to severe acute respiratory distress syndrome (ARDS). I/R injury is associated with increased short-and long-term morbidity and mortality [1,3,4]. During I/R injury, the graft organ develops structural damage, such as interstitial and intraalveolar oedema formation and loss of integrity of the blood-air barrier [5,6].…”
mentioning
confidence: 99%
“…However, primary graft dysfunction (PGD), infection, and rejection remain as important contributors to mortality after lung transplantation. PGD is the most common postoperative complication, occurring in 25% of recipients [10,11]. The treatment of PGD varies with the severity of lung injury, with general supportive care in low grade forms.…”
Section: Harefield Hospitalmentioning
confidence: 99%